Wear of different aluminum matrix composites under conditions that generate a mechanically mixed layer - Rosenberger, Mario Roberto (2005)
Wear experiments in a pin-on-ring apparatus were performed using aluminum matrix composite, in which the matrix alloy AA6061, was reinforced with Al 2O3, B4C, Ti3Al, and B2Ti in volume fractions ranging from 5% to 15%. The wear conditions generate in all cases a mechanically mixed layer (MML). The results were compared to those obtained with the non-reinforced alloy, which for the same conditions does not form the MML. The improvement of the wear properties was substantial, decreasing the wear rate in two orders of magnitude, result that is independent of volume fraction and nature of the reinforcement. The analysis of the surface and subsurface of the worn samples shows defects and presence of iron in the MML. These results indicate that different type of reinforcement can generate MMLs with similar wear resistance. Moreover, they are used to introduce new elements of analysis for the development of a mechanism of formation of the MML.